EXAMINATION IN AUDITING. - Meigs, Walter B. (The Accounting Review, 1961)
Abstract This article presents question and answer asked in the auditing section of the Uniform Certified Public Accountant examination on November 3, 1960. One question stated that Star Wholesale Co. is a wholesaler selling merchandise to local hardware and paint stores. The Coaton Paint Co. has sold its outdoor paint products to Star Wholesale Co. for years on regular terms. The candidates have to make adjustment of balance sheet account and recommend proper audit procedures. The answer to this question is, the auditor discovered the unsatisfactory control over consigned goods before the balance sheet date, he can and should request the client to segregate the consigned stock before taking the annual physical inventory. Verification of the consigned goods on hand by physical count is an essential step in determining the amount advanced to the consignor and the proper amounts for inventory and accounts payable. Another question is, in most medium-sized and large audits, it is customary for the auditor to select for detailed examination a series of items entered in the voucher register. The selection is from a period other than at year end. Answer to this question is, in medium-sized and large audits, primary emphasis is placed upon evaluation of internal controls rather than verification of any substantial portion of individual items in the accounts.